PENGARUH SOFT SKILL DAN PENGALAMAN MAGANG KERJA TERHADAP KESIAPAN KERJA MAHASISWA MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA MAHASISWA FEB UNIVERSITAS PGRI SEMARANG) - Herlisa Setiarini; Heri Prabowo; Sutrisno Sutrisno; Henry Casandra Gultom (EKOBIS, 2022)
The purpose of this study was to examine the independent variables, namely soft skills and work experience on the dependent variable of work readiness through work motivation as a mediating variable. The population in this study was students in the 2018 Faculty of Economics and Business (FEB) Department of PGRI Semarang University, which amounted to 167 people. Sampling in this study used a saturated sample. The sample in this study were all students of economics and business class 2018, totaling 167 people. Collecting data in this study using a questionnaire. The analytical method used is the Structural Equation Model (SEM) with Smart PLS 3.2.9 analysis tool. The results showed that the research model had met the validity and reliability of the construct on the SEM assumption with Smart PLS 3.2.9 so that the model was declared feasible. Based on data analysis, it can be concluded that: 1) Soft skills and work readiness of students of the Faculty of Economics and Business, PGRI University Semarang, 2) Internship experience and work readiness of students of the Faculty of Economics and Business, PGRI University Semarang, 3) Work motivation and work readiness of students of the Faculty of Economics and Business, PGRI University Semarang, 4) Soft skills and Work Motivation of Students of the Faculty of Economics and Business, PGRI University of Semarang, 5) Internship experience and work motivation of students of the Faculty of Economics and Business, PGRI University Semarang, 6) Indirect influence of soft skills on work readiness of Faculty Students Economics and Business PGRI Semarang University through work motivation, 7) Internship experience and work readiness Students of the Faculty of Economics and Business, PGRI University Semarang through work motivation